Experimental Investigation of Palm Kernel Shell and Cow Bone Reinforced Polymer Composites for Brake Pad Production - Afolabi, Mayowa; Abubakre, O.K; Lawal, S.A; Raji, Abdulkabir (International Journal of Chemistry and Materials Research, 2015)
Formulation of brake pad from palm kernel shell (PKS) and cow bone reinforced polymer composite was investigated. Palm kernel shell and cow bone were added in different sieve grading into an epoxy resin and hardener at 100, 100 and 120 sieve grading respectively. The formulated brake pads were characterized based on the requirements for brake pad uses. All properties investigated were observed to be within the acceptable requirement for brake pad function. The impact test for PKS and cow bone show 1.0 J and 1.5 J respectively. The hardness test show 55.7 HRB and 46.0 HRB values for PKS and cow bone respectively. While the water absorption test for PKS was 5.05% and cow bone was 5.53%. Oil absorption test for PKS was 2.23% and 4.16% for cow bone. The values of thermo-gravimetric analysis (TGA) were measured in terms of highest percentage weight loss and for PKS it was 57.14% and 63.24% for cow bone. While the values of coefficient of friction for PKS and cow bone were 0.735 and 0.677 respectively. Wear rate for PKS was 9.57E-7 and 1.44E-6 for cow bone. Crushing strength for PKS was 23N/mm² and 21N/mm² for cow bone.